English grammar for dummies, portable edition - Woods, Geraldine. (Wiley, 2006)
This book gives the latest techniques for improving efficiency with English grammar and punctuation. It teaches the rules of verbs, adjectives, and adverbs; prepositions, propositions, and pronoun pronouncements; punctuation; possessives; and proofreading skills for all communication.